Um olhar sobre as concepções de ciência e ensino de ciências de alunos-concluintes de química - RIBEIRO, Evandro Luiz da Luz (Universidade Federal do Pará, 2011)
The present study aim investigate the conceptions about science and science teaching on concluding students to Chemistry Teaching, the group of concluding of the second semester of 2004 in UFPA, summing 12 participators for the research. For the identification of the conceptions on science and science teaching, an assay was elaborated, previously tested with 15 concluding students on the course the biology whole licenciature, aiming to validate the investigation and post reformulation. The final version of the assay brought 12 questions, which the answers made possible the building of a schedule containing the answers of the participating subjects in the study. The analyses on this schedule instructed the creation of categories for the answers, with the identification of assignments of science and science teaching of Bacon, Comte, Popper. These authors and others allowed me to analyses the subjects markings and identify experimental inductive science, technology science, process science and conceptions of science teaching as a conceptual changing, set of handable activities and learning as means of construction.